2023
DOI: 10.2147/amep.s413816
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Virtual Teaching in a New Era of Medical Education: Lessons from a Neurology Course

Tamara Kaplan,
Christopher Tarolli,
Christopher Doughty

Abstract: The COVID-19 pandemic has led to a sudden shift toward virtual learning in neurology education, which presents challenges for educators. However, virtual learning is here to stay for three key reasons: demand among students, ease of dissemination, and potential to improve educational quality. Despite challenges, educators can teach effectively using appropriate virtual tools and methods, with innovative approaches that will ultimately lead to sustained improvements in neurology education. Here, we aim to help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…It created an unprecedented and significant impact on medical education globally. 1,2 Traditional education models offer in-person, instructor-led lessons, and clinical rotations with bedside teaching that allows medical students to have direct patient contact. 3 When traditional education was halted during the COVID-19 pandemic due to the closure of educational institutions, a majority of medical schools withdrew their students from hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It created an unprecedented and significant impact on medical education globally. 1,2 Traditional education models offer in-person, instructor-led lessons, and clinical rotations with bedside teaching that allows medical students to have direct patient contact. 3 When traditional education was halted during the COVID-19 pandemic due to the closure of educational institutions, a majority of medical schools withdrew their students from hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Online education has historically been viewed as an alternative pathway, one that is particularly implemented to enhance independent learning and improve access to educational materials. 1,2,8 Norman 9 suggested that a substantial portion of the clinical curricula should transition to simulation-based learning, recognizing an increasing gap between the suitability of clinical settings for learning and the real environment medical students are exposed to. Over the last decade, there have been attempts to integrate online learning strategies to both preclinical and clinical medical education.…”
mentioning
confidence: 99%